Leptin potentiates GABAergic synaptic transmission in the developing rodent hippocampus - Guimond, Damien; Diabira, Diabe; Porcher, Christophe; Bader, Francesca; Ferrand, Nadine; Zhu, Mingyan; Appleyard, Suzanne M.; Wayman, Gary A.; Gaiarsa, Jean-Luc (Frontiers in Cellular Neuroscience, 2014)
It is becoming increasingly clear that leptin is not only a hormone regulating energy homeostasis but also a neurotrophic factor impacting a number of brain regions, including the hippocampus. Although leptin promotes the development of GABAergic transmission in the hypothalamus, little is known about its action on the GABAergic system in the hippocampus. Here we show that leptin modulates GABAergic transmission onto developing CA3 pyramidal cells of newborn rats. Specifically, leptin induces a long-lasting potentiation (LLP-GABAA) of miniature GABAA receptor-mediated postsynaptic current (GABAA-PSC) frequency. Leptin also increases the amplitude of evoked GABAA-PSCs in a subset of neurons along with a decrease in the coefficient of variation and no change in the paired-pulse ratio, pointing to an increased recruitment of functional synapses. Adding pharmacological blockers to the recording pipette showed that the leptin-induced LLP-GABAA requires postsynaptic calcium released from internal stores, as well as postsynaptic MAPK/ERK kinases 1 and/or 2 (MEK1/2), phosphoinositide 3 kinase (PI3K) and calcium-calmodulin kinase kinase (CaMKK). Finally, study of CA3 pyramidal cells in leptin-deficient ob/ob mice revealed a reduction in the basal frequency of miniature GABAA-PSCs compared to wild type littermates. In addition, presynaptic GAD65 immunostaining was reduced in the CA3 stratum pyramidale of mutant animals, both results converging to suggest a decreased number of functional GABAergic synapses in ob/ob mice. Overall, these results show that leptin potentiates and promotes the development of GABAergic synaptic transmission in the developing hippocampus likely via an increase in the number of functional synapses, and provide insights into the intracellular pathways mediating this effect. This study further extends the scope of leptin’s neurotrophic action to a key regulator of hippocampal development and function, namely GABAergic transmission.